Pengembangan Media Pembelajaran ICT Berbasis Game Edukatif Wordwall Sajak Bahasa Sunda Di Sekolah Dasar - Syaripah, Auliya; Saputra, Erwin Rahayu (Jurnal Pendidikan Dasar dan Keguruan, 2024)
Technology that continues to develop has an impact on the world of education, including the use of ICT (Information, Communication and Technology) based learning media. This research aims to develop ICT-based learning media, namely educational word wall game-based learning media for class V students with Sundanese poetry material. The research method used in this research is the ADDIE development research method (Analysis, Design, Development, Implementation, and Evaluation). The steps for product development include analysis, design, development, implementation and evaluation. The students' response to this learning media was very good, none of the students were sleepy or bored of learning using game learning media because they were curious about what would happen afterward. The product developed in this research is ICT-based learning media based on wordwall educational games involving opening boxes and random name selection. The results of this research are that educational games learning media are very suitable to be used to support the learning of Sundanese poetry for class V elementary schools.